Integrating Food-Water-Energy Research through a Socio-Ecosystem Approach - Maass, Manuel (Frontiers in Environmental Science, 2017)
The nexus approach helps in recognizing the link between water, energy and food production systems, emphasizing the need to manage them in a more integrated way. The socio‑ecosystem (SES) approach, however, goes beyond that, by incorporating the regulation and supporting services in the management equation.  Changes in ecosystem integrity affect the delivery of ecosystem services to society, which affects local people’s well-being, creating a feedback mechanism regarding management strategies. The SES approach makes explicit the “human‑bio‑physical” nature of our interaction with ecosystems, highlighting the need for a more integrated and interconnected social‑ecological research perspective. In addition, the SES approach makes more explicit the multi-scale character of the ecological processes that structure and maintain social‑ecological systems. Water dynamics have an important role in shaping ecosystem’s structure and functioning, as well as determining the systems capacity for delivering provisioning services. The tropical dry-deciduous forest, is particularly useful in studying water-food-energy trade-off interactions. Recently, a category 5 hurricane landed in the study area (Mexico’s Pacific coast), triggering various social and ecological problems. This event is challenging the current forest management strategies in the region. The extreme hydrometeorological event created an excellent opportunity to test and promote the SES approach for more integrated food‑water‑energy research. By using the SES approach within our long-term socio-ecological research project, it was easier to identify opportunities for tackling trade‑offs between maintaining the transformation of the system and a more sustainable alternative: promoting the maintenance of the ecosystem’s integrity and its capacity to deliver provisioning and regulating services.